PELATIHAN PENERAPAN PROJECT BASED LEARNING BAGI GURU SEKOLAH MENENGAH KEJURUAN DI KABUPATEN MALANG - Mustaji, Mustaji; Arianto, Fajar; Diningrat, Syaiputra W.M.; Shofiana, Fahlulia Rahma (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
The dynamics of development and integration of information technology in education require the application of innovative learning strategies, methods and models, one of which is the Project-Based Learning (PjBL) model. This model is effective in developing students' 21st century skills such as critical thinking, creativity, and collaboration. However, the facts in the field show that most teachers in SMK Malang Regency do not understand the concept or implementation of PjBL. This study aims to improve teachers' understanding and skills in implementing PjBL through training designed based on the ADDIE model, namely: (1) training needs analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. This training was attended by 14 SMK teachers in Malang Regency with teaching backgrounds in Animation, Visual Communication Design, Network Computer Engineering, and Broadcasting subjects with blended training methods (face-to-face and online) on 22 May 2024, 24 May 2024, 30 May 2024, and 6 June 2024. The evaluation results showed significant improvement in teachers' understanding and skills in designing PjBL-based learning tools, with a final average score of 87.8. The training made a positive contribution in supporting teachers to adapt and develop project-based learning in vocational schools, in line with the demands of international education quality standards implemented at SMKN 1 Singosari Malang. The output of this activity produced training materials in the form of powerpoint, video documentation and online mass media publications.